2009
DOI: 10.1155/2009/390951
|View full text |Cite
|
Sign up to set email alerts
|

Association of MCP-1 -2518 A/G Single Nucleotide Polymorphism with the Serum Level of CRP in Slovak Patients with Ischemic Heart Disease, Angina Pectoris, and Hypertension

Abstract: The aim of our work was to find if MCP-1 -2518 (A/G) single nucleotide polymorphism (SNP) influences somehow the serum concentrations of high-sensitive CRP (hsCRP) both in patients suffering from ischemic heart disease (IHD), myocardial infarction (MI), angina pectoris (AP), and hypertension (HT) and in control group of healthy subjects. Totally, 263 patients with the diagnosis of IHD, out of them 89 with MI, 145 with AP, 205 with HT, and also 67 healthy subjects were included in the study. First, we estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It was also detected in human cardiac myocytes and human cardiac fibroblasts which revealed CCL2 production under cytokine stimulation, but not under hypoxia, in vitro [ 45 ]. In patients with ischemic cardiomyopathy, polymorphism in CCL2 gene (CCL2-2518 A/G single nucleotide polymorphism) was correlated with C-reactive protein (CRP) level [ 46 ]. Altogether these findings suggest that this chemokine is more associated with inflammation than with hypoxia/ischemia, being strongly regulated by reperfusion and correlated with a known inflammatory marker such as CRP.…”
Section: Cardiovascular Disease From Ischemia To Heart Failurementioning
confidence: 99%
“…It was also detected in human cardiac myocytes and human cardiac fibroblasts which revealed CCL2 production under cytokine stimulation, but not under hypoxia, in vitro [ 45 ]. In patients with ischemic cardiomyopathy, polymorphism in CCL2 gene (CCL2-2518 A/G single nucleotide polymorphism) was correlated with C-reactive protein (CRP) level [ 46 ]. Altogether these findings suggest that this chemokine is more associated with inflammation than with hypoxia/ischemia, being strongly regulated by reperfusion and correlated with a known inflammatory marker such as CRP.…”
Section: Cardiovascular Disease From Ischemia To Heart Failurementioning
confidence: 99%
“…A correlation between higher plasma CRP level and presence of CD14 260TT homozygous allele was also found, which could be associated with the higher ability of macrophages to become activated and produce pro-inflammatory cytokines (Bernardo et al, 2006;Espliguero et al, 2005). Bucova et al (2009a) found an association of MCP-1 -2518 A/G single nucleotide polymorphism with the serum level of CRP in Slovak patients with ischemic heart disease, angina pectoris, and hypertension. Additionally, a genome-wide association study has been performed among 6 345 apparently healthy women in whom 336 108 single nucleotide proteins were evaluated as potential determinants of plasma CRP concentration (Devaraj, 2010).…”
Section: Genetics Of Crpmentioning
confidence: 79%
“…The study, which is based on the analysis of 13 studies (Szalai et al, 2001;Simeoni et al, 2004;Cermakova et al, 2005;McDermott et al, 2005;Bjarnadottir et al, 2006;Bucova et al, 2008;Cam et al, 2008;Jemaa et al, 2008;Bucova et al, 2009aBucova et al, , 2009bZhang et al, 2009;van Wijk et al, 2010;Zhong et al, 2010), found a probable increase in CAD with the MCP-1 -2518G allele in a population of Caucasian. However, the result might have been caused by publication bias and insufficient sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one case-only study (Alioglu et al, 2009) and two family-based studies (McGlinchey et al, 2004;Kim et al, 2007) were also excluded. Finally, 21 studies (Szalai et al, 2001;Simeoni et al, 2004;Cermakova et al, 2005;McDermott et al, 2005;Bjarnadottir et al, 2006;Iwai et al, 2006;Cam et al, 2008;Bucova et al, 2008;Jemaa et al, 2008;Bucova et al, 2009a;Bucova et al, 2009b;Zhang et al, 2009;Zhong et al, 2010;van Wijk et al, 2010;El Mahgoub et al, 2011;Lin et al, 2012;Wang & Zhang, 2012;Yang et al, 2012;Xu et al, 2013;Kaur et al, 2013;Nasibullin et al, 2014) with a total of 8,735 cases and 12,300 controls were included in this meta-analysis. The process of the study selection and exclusion is shown in Figure 1.…”
Section: Eligible Studies Included In the Meta-analysismentioning
confidence: 99%